Areas of endemism in the Southwestern Atlantic Ocean based on the distribution of benthic hydroids (Cnidaria: Hydrozoa) - Miranda, Thaís Pires (2015)
Geographic distributions of 130 species of benthic hydroids were used to infer areas of endemism in the Southwestern Atlantic Ocean (SWAO, between 22°S and 55°S). Endemicity Analysis (EA) was carried out with the software NDM VNDM, using a 2° x 2° grid with different values of F (F = 0.5 and F = 1.0) for inferred presence. Hypothesized areas of endemism (16 with F = 0.5 and 13 with F = 1.0) formed three generalized patterns: (1) Tropical, (2) Subtropical, and (3) disjunctions along Tropical and Subtropical areas. Areas of endemism estimated here were compared with provinces, ecoregions and areas of endemism previously defined (but not based on algorithmic analysis) in the literature. Ecological and historical aspects that are potentially relevant for the SWAO realm were contrasted, related and discussed to areas of endemism. This is the first study to apply NDM VNDM to the marine realm and one of the few that focuses on the SWAO.